O Instituto Geográfico e Histórico do Amazonas e os itinerários da construção de um campo intelectual em Manaus-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
Understanding the process of constituting an intellectual field in the cultural scene of Manaus in the early twentieth century is a task that requires the effort to understand the connections between the intellectual universe and the political sphere, understood as a field of power. An example of this connection, the founding of the Amazonas Geographical and Historical Institute (IGHA) represents the initiative of a group of intellectuals who, in a context of difficulties for the permanence of scientific and cultural institutions, dared to found an entity with clear intentions of think about reality and propose possible paths to the moment of economic crisis verified in those years of the 1910s. Appearing in the cultural landscape of Manaus in 1917, IGHA now brings together intellectuals and personalities from other social spheres of reality, proposing, among other activities, the edition of a magazine for the publication of the work of its associates. Following the pioneering model of the Brazilian Historical and Geographic Institute (IHGB), founded in 1938 in Rio de Janeiro, IGHA will follow a path of proximity with the political field, in order to make use of the volume of relationship capital accumulated by its members to It is then constituted as a recognized place of speech capable of recognizing positions internally taken by the founders and effective partners. From the connection between the internal procedures of establishing a modus operandi and a conductor-oriented habitus and the pressures from the broader social order, especially from the political-economic world, the work sought to understand the intentions at stake in the founding of the Institute. , the networks of relationships established throughout its history and the role it has assumed in the process of developing a relatively autonomous intellectual field in the city of Manaus and the Amazon.
Keywords: Instituto Geográfico e Histórico do Amazonas; Vida intelectual - Manaus - Século XX; Cultura - Manaus - Século XX; CIÊNCIAS HUMANAS; Campo intelectual; Campo cultural; Institutos históricos